AGGREGATION WITH SEQUENTIAL NON-CONVEX PUBLIC - AND PRIVATE - SECTOR LABOR SUPPLY DECISIONS - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields, 2016)
This paper explores the problem of non-convex labor supply decisions in an economy with both private and public sector jobs. In contrast to Vasilev (2015a), the sectoral labor choice is made in a sequential manner. Still, the micro-founded representation obtained from explicit aggregation over homogeneous individuals again features different disutility of labor across the two sectors. Thus, there is little merit in the timing of the sectoral non-convex labor choice.